Development strategies and application of antimicrobial peptides as future alternatives to in-feed antibiotics - Liang, Qingping; Liu, Zhemin; Liang, Ziyu; Zhu, Changliang; Li, Dongyu; Kong, Qing; Mou, Haijin (The Science of the total environment, 2024)
The use of in-feed antibiotics has been widely restricted due to the significant environmental pollution and food safety concerns they have caused. Antimicrobial peptides (AMPs) have attracted widespread attention as potential future alternatives to in-feed antibiotics owing to their demonstrated antimicrobial activity and environment friendly characteristics. However, the challenges of weak bioactivity, immature stability, and low production yields of natural AMPs impede practical application in the feed industry. To address these problems, efforts have been made to develop strategies for approaching the AMPs with enhanced properties. Herein, we summarize approaches to improving the properties of AMPs as potential alternatives to in-feed antibiotics, mainly including optimization of structural parameters, sequence modification, selection of microbial hosts, fusion expression, and industrially fermentation control. Additionally, the potential for application of AMPs in animal husbandry is discussed. This comprehensive review lays a strong theoretical foundation for the development of in-feed AMPs to achieve the public health globally. [Display omitted] •Antimicrobial peptides (AMPs) are potential antibiotic alternatives for application in feed.•Multiple mechanisms and broad-spectrum of AMPs reduce microbial resistance emergence.•AMPs promote animal growth, regulate gut microbiota, and improve disease resistance.•Weak activity and stability, and low yield are limitations for AMPs application.•Development strategies like gene engineering may improve in-feed AMPs properties.